2008
DOI: 10.1017/s0025315408000611
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasites in an intermediate host population near its southern border: the common cockle (Cerastoderma edule) and its trematodes in a Moroccan coastal lagoon (Merja Zerga)

Abstract: The metazoan parasite community of Cerastoderma edule was studied in the southern geographical range of the host (the coastal lagoon Merja Zerga, Morocco). A total of 11 metazoan species was found in cockles. Nine of these were trematodes using cockles as either first intermediate host (three species) or second intermediate host (six species). In addition, two other endo-metazoan species (Pinnotheres pisum and Paravortex cardii) were recorded from cockles in the studied lagoon. All the observed metazoans in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 29 publications
3
57
0
1
Order By: Relevance
“…Conversely, for RO, Meiogymnophallus minimus com pletely disappeared from cockles (−99.9%), precluding the hypothesis that the more infected cockles died. No metacercariae were hyperparasitized, as observed elsewhere (Carballal et al 2005, Gam et al 2008, and environmental conditions at Arguin are potentially suitable for infection to develop, as this parasite is present in the transplant area (de Montaudouin & Lanceleur 2011). Although transplantation can be a general explanation for M. minimus mor tality, this study found that the lifespan of the metacercariae can be shorter than that of their host, and therefore one must be careful in always attributing a decrease in metacercariae in the host to parasitedependent mortality (Anderson & Gordon 1982, Kennedy 1984, Desclaux et al 2004).…”
Section: Parasite Dynamicsmentioning
confidence: 48%
“…Conversely, for RO, Meiogymnophallus minimus com pletely disappeared from cockles (−99.9%), precluding the hypothesis that the more infected cockles died. No metacercariae were hyperparasitized, as observed elsewhere (Carballal et al 2005, Gam et al 2008, and environmental conditions at Arguin are potentially suitable for infection to develop, as this parasite is present in the transplant area (de Montaudouin & Lanceleur 2011). Although transplantation can be a general explanation for M. minimus mor tality, this study found that the lifespan of the metacercariae can be shorter than that of their host, and therefore one must be careful in always attributing a decrease in metacercariae in the host to parasitedependent mortality (Anderson & Gordon 1982, Kennedy 1984, Desclaux et al 2004).…”
Section: Parasite Dynamicsmentioning
confidence: 48%
“…Shedding and transmission of trematode larvae is known to be temperature dependent (Jensen et al 1999, Gam et al 2008, Thieltges 2008. In temperate tidal areas the period of infection is spring to autumn (Desclaux et al 2006, Thieltges 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Fermer et al (2009) found the acquisition of metacercariae was associated with shell length when cockles were smaller, but this was less important in older cockles. However, others have found no relationship between size and intensity (Gam et al 2008). The assumption that larger cockles would have a higher intensity of trematodes is based on larger cockles having larger siphons and in gesting cercariae with greater ease.…”
mentioning
confidence: 99%
“…For this purpose, the more complex sessile invertebrate disease models, including contact with or filtration of waterborne pathogens and particle diffusion processes, are built up from those simpler contact-based SI models applied to fish and mammal diseases. The models presented here do not cover facultative bacterial parasites (Kazama and Fuller 1977) or complex life cycles of protozoan (Robertson 2007) or metazoan parasites (Gam et al 2008) requiring intermediate hosts.…”
Section: Theoretical Basis For the Modelsmentioning
confidence: 99%